The Implementation of the Duties of Officials Making Land Deeds in Making Deeds of Sale and Purchase of Land During the Implementation Period of Restricting Community Activities - Alaric, Muhammad Eldin Naufan (Jurnal Konstatering, 2022)
Land Deed Officials/PPAT are officials who are authorized to make authentic deeds that can be trusted. Making a Land Sale and Purchase Deed is a document made by a Land Deed Making Officer (PPAT) which can prove an agreement between each party regarding the sale and purchase of land. During the period of the spread of Covid-19 in Indonesia and government regulations regarding the imposition of restrictions on community activities (PPKM), in this case officials making land deeds and appearers must follow all applicable rules to minimize and break the chain of the spread of Covid-19 in Indonesia. This study uses an empirical juridical approach, analytical descriptive research specifications, namely how to describe the condition of the object under study, the method of data collection is done by interviews and literature studies, as well as qualitative analytical methods as a method of analyzing data. Based on the results of the research and discussion: 1) PPAT has an important role, namely a General Official who helps the parties to achieve their wishes, prepares and registers a transfer of land rights at the Land Office, and has the authority to make AJB as an authentic deed, and implements health protocols in making a sale and purchase deed in accordance with the rules issued by the government; 2) Obstacles in making a land sale and purchase deed, namely if one of the parties is infected with Covid-19, it is mandatory to temporarily postpone the implementation of the signing of the document, the solution in making a land sale and purchase deed during the implementation of restrictions on community activities due to the Covid-19 outbreak, namely by adhering to the health protocols that have been recommended by the government to the public.Keywords: Land; Official; Purchase.